2021
DOI: 10.1186/s12957-021-02399-9
|View full text |Cite
|
Sign up to set email alerts
|

Breast myeloid sarcoma presenting as a palpable breast lump after allogeneic stem cell transplantation for acute myelomonocytic leukemia: a rare case report

Abstract: Background Myeloid sarcoma (MS) is a tumor secondary to myeloid leukemia that consists of immature granulocytes with or without mature granulocytes and is a rare extramedullary manifestation of acute myeloid leukemia (AML). Case presentation We report a case of a 34-year-old woman diagnosed with AML-M4 who achieved remission after chemotherapy and received allogeneic stem cell transplantation (allo-SCT) for consolidation. Her past medical history s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Even so, an intensive chemotherapy regimen might not be ideal in relapsed patients because they have a higher probability of having a poor general condition or weak immunity due to the previous chemotherapy. There was a case report where a 34-year-old female patient with relapsed AML involving breast received chemotherapy, but died of respiratory failure within one year of treatment ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even so, an intensive chemotherapy regimen might not be ideal in relapsed patients because they have a higher probability of having a poor general condition or weak immunity due to the previous chemotherapy. There was a case report where a 34-year-old female patient with relapsed AML involving breast received chemotherapy, but died of respiratory failure within one year of treatment ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…US findings are variable and include homogeneous or heterogeneous hypoechoic lesions that are hypervascularized on color Doppler scans and cannot be easily distinguished from benign lesions [ [15] , [16] , [17] ]. Additionally, MRI can be a valuable diagnostic tool with breast MS presenting as hypointense lesions on T1-weighted images, hyperintense on T2-weighted images, and with inhomogeneous enhancement [18] . While nonspecific, these findings are suspicious and warrant a biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…These patients typically have a good response to chemotherapy and high complete remission rate when treated with high dose cytarabine (HiDAC) plus anthracycline/anthracenedione-based induction therapy [ 19 , 20 ]. Most common induction regimen includes “7+3” therapy (7 days of cytarabine (Ara-C) followed by 3 days of idarubicin (4-demethoxydaunorubicin)) [18] . It is recommended to perform a bone marrow aspirate and biopsy 14-21 days after the start of the induction therapy to evaluate the efficacy of the treatment [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid sarcoma (MS; also known as granulocytic sarcoma or chloroma) is a solid extramedullary mass composed of primitive myeloid cells that disrupts the normal architecture of the tissue in which it is found. MS can present concurrently with acute myeloid leukemia (AML), precede the diagnosis of AML without evidence of leukemia in the blood or bone marrow or as a relapse in a patient with previously treated AML [ 1 , 2 , 3 ]. In children, the overall incidence of MS in association with AML varies, but has been reported to be as high as 24% [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Figurementioning
confidence: 99%
“…Flow cytometry revealed that the blasts expressed CD34, CD13, CD33, CD117, and CD40. She was classified as CNS [2]. Chromosomal analysis demonstrated 46,XX,der(21)t(8;21)(q22;q22)ins (5;21) (q12q21;q22) [20], and fluorescence in situ hybridization (FISH) analysis demonstrated RUNX1-RUNX1T1/t(8;21) variant gene fusion in 98.5% of cells and gain of chromosome 15q24 in 7% of cells.…”
mentioning
confidence: 99%